THE NIGERIA MILITARY AND THE FIGHT AGAINST ISLAMIC STATE`s WEST AFRICA PROVINCE (ISWAP), 2016-2022 - BABA ALI KELLU; RUTH CALEB LUKA LUKA; MOHAMMED BELLO BABAN’UMMA (International Studies Journal)
This paper critically evaluates the resilience of the Islamic State West Africa Province (ISWAP) amidst ongoing conflicts with the Nigerian military from 2016 to 2022. Utilizing Attachment Theory as a framework, the research delves into the persistence and adaptive tactics of ISWAP against military strategies. Through surveys and in-depth interviews, the study assesses the effectiveness of Nigeria's counter-insurgency efforts and identifies the challenges faced by the military and its allies. The findings from the study revealed that there were several offensives by the Nigerian military against ISWAP with the aim of neutralizing their fighters by destroying their camps and hideouts and restoring peace and security in the affected areas, certain strategies exhibit significant shortcomings, necessitating continuous refinement. The research underscores the complex, evolving nature of the ISWAP insurgency and the need for a multifaceted, adaptive approach in counterterrorism. It contributes to understanding insurgency dynamics and emphasizes the importance of regional military collaboration, particularly through the Multinational Joint Task Force (MNJTF). The study recommends the need for increase in intelligence gathering in order to identify and neutralize ISWAP’s leadership and financing sources, and to collaborate with neighbouring countries of Niger, Chad, and Cameroon for better intelligence sharing, as it will help in reducing civilian casualties by improving targeting and verification processes during operations.